Self medication in the age of connectivity and its risks - the case report - Kościuk, Andrzej; Kos, Michał; Drankowska, Justyna; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Introduction: Public healthcare systems throughout the world are strained by demographic changes, soaring costs and insufficient resources. This can negatively affect access to health services, which forces patients to seek other treatment options. Websites and online forums have become one of the most common sources of health advice, with online medicine trade burgeoning as well. However, while the internet provides vast knowledge database, using unverified advice or product can have dangerous consequences. We present a patient with acute amphetamine poisoning, caused by ingestion of substance marketed online as weight loss drug. Aim of study: to discuss potential risks and problems of using online advice and products in self medication Results: Our patient, the 36 year old female, was admitted to Department of Toxicology and Cardiology with symptoms suggestive of poisoning of some kind. She admitted to using a weight- loss medication throughout the last month, in increasing dosages. The drug was bought from online trading platform. She lost 8 kilograms of body weight through this period. Subsequently, she noticed some disturbing symptoms, including dystonia movements of limbs, paresthesia in right half of the body and blurred vision. Episodes of tachycardia were reported as well. On admission, the patient was weakened and mildly depressed. She reported not eating anything for the last 2 days. Toxicological examination revealed the presence of psychoactive substances in the urine- amphetamine at 7800 ng/ml and LSD at 1,08ng/ml. Our patient was consulted by psychiatrist and psychologist. Fluid therapy was applied, along with Relanium, low molecular weight heparin, Dexaven and Polprazol. Due to elevated blood pressure, a 24-hour blood pressure measurement was performed. Next, hypotensive therapy was administered. The patient’s condition improved and she was discharged from the hospital after 4 days, with scheduled control in ambulatory setting and recommendation of beginning the psychotherapy. Conclusions: Online health advice and products can be dangerous if used inappropriately. A focus on education and provision of freely available, high quality medical information can make it safe and useful complement to healthcare systems throughout the world. Appropriate systems controlling online medicine distribution should also be instituted, with patients’ safety and wellbeing as prime goals.